Fatal poisoning of four workers in a farm: Distribution of hydrogen sulfide and thiosulfate in 10 different biological matrices. (November 2020) - Moretti, Matteo; Ballardini, Marco; Siodambro, Chiara; Tronconi, Livio; Osculati, Antonio Marco Maria; Freni, Francesca; Vignali, Claudia; Morini, Luca
Highlights: We report an accidental poisoning by hydrogen sulfide involving 4 farmers. Sulfide and thiosulfate were evaluated in 10 different biological matrices. We discuss the not homogeneous toxicological values detected in samples. Toxicological analyses contributed to understand the sequence of the events. Abstract: We evaluate the distribution of sulfide and thiosulfate (TS) in biological samples of four dairy farmers died inside a pit connected to a manure lagoon. Autopsies were performed 4 days later. Toxicological analyses of sulfide and TS were made using an extractive alkylation technique combined with gas chromatography/mass spectrometry (GC/MS). Autopsies revealed: multiorgan congestion; pulmonary edema; manure inside distal airways of three of the four victims. Sulfide concentrations were cardiac blood: 0.5–3.0 μg/mL, femoral blood: 0.5–1.2 μg/mL, bile: <0.1–2.2 μg/mL; liver 2.8–8.3 μg/g, lung: 5.0–9.4 μg/g, brain: 2.7–13.9 μg/g, spleen: 3.3–6.3 μg/g, fat: <0.1–1.5 μg/g, muscle: 2.6–3.5 μg/g. TS concentrations were cardiac blood: 2.1–4.9 μg/mL, femoral blood: 2.1–2.3 μg/mL, bile: 2.5–4.4 μg/mL, urine: <0.5–1.8 μg/mL; liver <0.5–2.6, lung: 2.8–5.4 μg/g, brain: <0.5–1.9 μg/g, spleen: 1.2–2.9 μg/g, muscle: <0.5–5.6 μg/g. The cause of death was assessed to be acute poisoning by hydrogen sulfide (H2 S) for all the victims. Manure inhalation contributed to the death of three subjects. The measurement of sulfide and TS concentrations in biological samples contributed to better understand the sequence of the events. Subjects 3 provided the highest concentration of sulfide in brain, thus, supporting the hypothesis of a rapid loss of consciousness and respiratory depression. One by one, the other farmers entered the pit in attempts to rescue the coworkers but collapsed. Despite the rapid death, subject 3 was the only one with TS detectable in urine. This could be due to differences in metabolism of H2 S.